THE IMPORTANCE OF CONCEPT AS AN OBJECT OF LINGUISTIC RESEARCH - Javliyev Mansurbek Odil o’g’li (Scholar Express Journal, 2024)
Linguistic encyclopedic dictionary, the concept is expressed through the meaning of the notion. Concept - 1) subject in the form of generalized opinion in reaction to events; 2) the term concept is used more often than concept when describing highly generalized grammatical and semantic phenomena. Concept (concept) is a phenomenon that has the importance of a word, but is considered as a system of different relations: meaning is in the language system, concept is a system of logical relations, and linguistics is also studied in the studies of logic. As a result of convergence of the sciences of linguistics and logic, the concept is falling out of use instead of words such as "event", "process", "evidence".
Keywords: Linguistic encyclopedic dictionary; Concept